1971
DOI: 10.1111/j.1432-1033.1971.tb01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of δ‐Aminolevulinic Acid Synthetase by Drugs and Steroids in vivo and in Isolated Perfused Rat Liver

Abstract: 8-Aminolevulinic-acid-synthetase induction by drugs depends upon the nutritional state of the animal. I n allylisopropylacetamide-treated animals the enzyme induction is reduced in fed compared with starved rats whereas after phenobarbital treatment an induction of the enzyme seen in starved animals is not observed in fed rats. 8-Aminolevulinic-acid-synthetase induction is studied in relation to the synthesis of cytochrome P450.I n the isolated rat liver perfused with either rat blood or washed bovine erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Administration of cortisol to starved shamoperated rats increased both holoenzyme and total pyrrolase activities by 50% (P=0.005-0.001) and did not therefore alter the haem-saturation ratio. Liver 5-aminolaevulinate synthase activity in fed rats is half of that in starved rats (Bock et al, 1971), and this is confirmed by our results with sham-operated animals ( Table 1). In agreement with the finding by Marver et al (1966), cortisol does not exert a significant effect on synthase activity in control (sham-operated) rats (Table 1), and this is consistent with the inability of the hormone to alter the haem-saturation ratio of tryptophan pyrrolase.…”
Section: Resultssupporting
confidence: 88%
“…Administration of cortisol to starved shamoperated rats increased both holoenzyme and total pyrrolase activities by 50% (P=0.005-0.001) and did not therefore alter the haem-saturation ratio. Liver 5-aminolaevulinate synthase activity in fed rats is half of that in starved rats (Bock et al, 1971), and this is confirmed by our results with sham-operated animals ( Table 1). In agreement with the finding by Marver et al (1966), cortisol does not exert a significant effect on synthase activity in control (sham-operated) rats (Table 1), and this is consistent with the inability of the hormone to alter the haem-saturation ratio of tryptophan pyrrolase.…”
Section: Resultssupporting
confidence: 88%
“…Enzymes were tested in liver homogenates. ALA synthetase was normally assayed with a radiochemical procedure according to Ebert et al [1970] and frequently checked by a colorimetric method as described in more detail in a previous publication [Bock et al, 1971]. Only the mi tochondrial form of the enzyme can be detected with our methods.…”
Section: Methodsmentioning
confidence: 99%
“…Unless otherwise indicat ed, food was withheld 24 h before hepatectomy. Livers were perfused with 70 ml Eagle minimal essential medium containing 25% bovine erythrocytes, 2% bovine serum albumin, and 0.1% heparin as previously described [Bock et al, 1971Matern et al, 1972]. Enzymes were tested in liver homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…In this report the perfused liver was chosen as a model for intact cells since in this (a) Absorption of a lipid-soluble substrate for UDPglucuronyltransferase (XOH); (b) enzyme reaction within the endoplasmic reticulum (UDP-GlcUA = UDP-glucuronic acid); (c) transport and secretion of glucuronides (X-GlcUA) into the bile and the blood or perfusate system an accurate time course and balance sheet of product formation can be established, while the cellular metabolism is close to that operating in vivo. The functional state of this model system has been previously characterized by its ability to synthesize albumin [l 11 and by the induction of enzymes [12]. 1-Naphthol was chosen as substrate since there are only two major pathways for its metabolism, leading to the glucuronide and sulfate conjugates 11 31.…”
mentioning
confidence: 99%